Durability of neutralizing antibodies against yellow fever virus after vaccination in healthy adults. Issue 17 (24th April 2023) - De Santis, Riccardo; Faggioni, Giovanni; Amoroso, Alessandra; Ciammaruconi, Andrea; Pomponi, Alice; Stella Lia, Maria; Amatore, Donatella; Molinari, Filippo; Petralito, Giancarlo; Stefanelli, Paola; Rezza, Giovanni; Lista, Florigio
Abstract: In accordance with the World Health Organization, one dose of yellow fever vaccine may guarantee protection lifelong in healthy adults. However, relatively little information is still available from ad hoc studies. We evaluated the persistence of neutralizing antibodies, which are considered to be an immune correlate of protection, in a large number of military personnel vaccinated up to 47 years before. Overall, 322 individuals were studied. The median time from vaccination to blood collection for neutralizing antibody evaluation was 9 years, ranging from <1 to 47 years. Of the 322 participants, 319 had neutralizing antibodies (99.1 %). The highest median PRNT50 value was observed in those vaccinated ≤1 year before (median PRNT50 = 320). In conclusion, our study confirms on a larger scale that, in healthy adults, neutralizing antibodies may persist as long as 47 years after a single yellow fever vaccines dose.